Pastiching as Artistic Research: Ifigenia / Ipermestra (Brussels, 2006)* - Forment Bruno (Musicology Today, 2021)
On 6 December 2006, students of the Royal Conservatoire of Brussels performed two one-act pasticci arranged by the author of this article: Ifigenia and Ipermestra. Assembled as experiments in the young discipline of artistic research in music, both ‘cut & paste’ operas offered opportunities to explore issues of music-dramatic syntax in opera seria. In this article, I explain how individual arias and recitatives were combined into two meta-compositions that sometimes respected, and sometimes overrode eighteenth-century generic conventions. By revisiting the scores, libretti, archives and first-hand memories pertaining to this venture, I will show that ‘pastiching’ (pasticciare) is more than a historical form; it is a transhistorical method, involving a broad network of agencies, operators, and stakeholders whose strategies can be artistic and non-artistic, convergent and divergent. Pastiching does not necessarily result in ‘works’, fixed in time and space, but rather produces meta-compositional assemblages, the transience and formal instability of which provide opportunities to showcase neglected repertoire and tackle outdated musical ontologies.